Pengaruh Animated Interactive Multimedia terhadap Pengetahuan Remaja Awal Tentang TRIAD KRR - Washli Manash S.Kep, Mohammad; Dr. Sri Sumaryani, Ns., M.Kep., Sp.Mat (Universitas Muhammadiyah Klaten, 2025)
Reproductive health in adolescents is an important issue, especially given the high risks faced by this group, including early pregnancy, sexually transmitted infections (STIs), and drug abuse. This study aims to evaluate the impact of interactive multimedia in the form of animation on the improvement of early adolescent knowledge about the Adolescent Reproductive Health TRIAD (TRIAD KRR). The research was carried out at SMP Muhammadiyah 1 Yogyakarta with two groups: the experimental group that received education through animated videos and the control group that did not receive intervention. Wilcoxon's test results for the control group showed a significant difference between pre-test and post-test values, with Asymp values. Sig. (2-tailed) of 0.000 (p < 0.05), even without animated multimedia intervention. Similarly, the experimental group showed the results of the Wilcoxon test with a significant difference between the pre-test and post-test values, with the Asymp value. Sig. (2-tailed) of 0.000 (p < 0.05), suggesting that animated multimedia interventions contribute positively to adolescent knowledge improvement. Analysis using the Mann-Whitney test also showed a significant difference in the level of knowledge between the experimental group and the control group, with values of Z = -3.582 and Asymp. Sig. (2-tailed) of 0.000 (p < 0.05). This indicates that the experimental group that received education through animated videos had a better level of knowledge compared to the control group. The average score for the experimental group was higher (Mean Rank = 37.82) than for the control group (Mean Rank = 32.38). Based on these results, it can be concluded that education through animated videos has a significant influence on increasing adolescents' knowledge about TRIAD KRR.